PENGARUH PENGAWASAN, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI PADA PT. SAKAPATAT MASAMAR SOSIAL) - Tantri Widiastuti; Tri Bodroastuti; Dina Murtiana (Universitas Islam Nahdlatul Ulama Jepara, 2020)
The purpose of this research was to analyze the influence of supervision, discipline of work and motivation on employee performance at PT. Sakapatat Masamar Sosial. The populations of this research were all employees of PT. Sakapatat Masamar Sosial which amounted to 94 people. The entire population is sampled so that this research is a census study. The analysis technique used was multiple liniear regression. The result of this research has shown that variable of supervision, discipline of work and motivation either partially or simultaneously has a significantly positive effect on employee performance.